Pengaruh Bahan Organik dan Suhu Pengeringan terhadap Ketahanan Hidup Aspergillus niger dalam Pupuk Pelet Bio-fosfat - Yudi Sastro; Donny Widianto; Irfan D. Prijambada (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
This research was aimed to investigate the effect of organic matter and drying temperature on Aspergillus niger survivability in the rock phosphate pellet fertilizer namely bio-phosphate. The research was arranged by a completely randomized design 3x3x6. Addition of the mixing of tapioca waste, rice bran, and starch (BOC) and the humic substance (BH) in the bio-phosphate, and its drying temperature (SP) were the treatments. Aspergillus niger inoculums survivability in the bio-phosphate was determined using plating methods. The result showed that the addition of BOC decreased amount of A. niger in the bio-phosphate up to 28.0%, while the BH increased the amount of A. niger up to 24.4%. The ideal drying temperature of bio-phosphate pellet fertilizer was 600C.